The association between children eating behaviour and physical activity during COVID-19 / Nurul Diyana Sanuddin ... [et al.] - Sanuddin, Nurul Diyana; Mohd Saleh, Maisarah; Abd Rahman, Siti Aishah; Wan Mohd Norsyam, Wan Mohd Norsyam; Linoby, Adam (Universiti Teknologi MARA, 2023)
The pandemic of Coronavirus (COVID-19) has resulted in the imposition of home confinement and the indefinite extension of school closures. Several countries, including Malaysia, have enacted 'lockdowns,' which prohibit people from engaging in outside activities. During this period, it leads to severe repercussions on individuals' eating and lifestyle behaviour. These behaviours increased the risk susceptibility to weight gain, particularly if the quantity of daily physical activity was reduced as a result of the lockdowns period. There is a need to draw attention to the pandemic's long-term impact on children's eating behaviour and physical activity. Clearly, social isolation and stay-at-home orders issued in cities around the world restrict opportunities for children to engage in physical activity. In addition, COVID-19 may aggravate the risk of a shift towards an obesity epidemic among children. It is critical to tackle children's eating and lifestyle behaviours during COVID-19 pandemic as these are intrinsically linked to the children's cognitive development, academic performance, and disease susceptibility. The purpose of the activity was to examine the association between the scores of the Children's Eating Behaviour Questionnaire (CEBQ), Physical Activity Questionnaire (PAQ-C) and Body Mass Index (BMI) among selected school children in Pahang during COVID-19. A total of 100 schoolchildren (37 males and 63 females) parents with children aged between 9-12 years completed an online survey which included a set of questionnaires to measure their own level of physical activity (PAQ-C) as well as that of their children's eating style (CEBQ) during the lockdown period. During COVID-19, schoolchildren are not engaged in physical activity, it showed that only 32 children active compared to 68 children were inactive on doing physical activity per week. Predominantly, children underweight was 39, Normal BMI was 38 children, overweight was 21 children and obesity children was 2, from this descriptive data it showed that enjoyment of food and food responsiveness are related in this study. The Pearson Analysis indicated that there were significantly associated with BMI and CEBQ (P = 0·006 to < 0·001). The physical activity scales revealed positively related to BMI (P = 0·048 to < 0·001). In conclusion, the current findings underlined the growing need for strategies in preserving children's health and development.